LEUKOCYTE VIRUS AND IMMUNOLOGICAL RESPONSE OF THE BODY - Qarshievich, Butaev Makhmud; Salimovich, Salimov Khait; Egamberdievich , Ruziev Zohid (Journal of Medical Genetics and Clinical Biology, 2024)
This study examined the immunological condition of cattle infected with spontaneous leukosis. Specifically, it compared the levels of immunoglobulins in cattle infected with leukosis viruses from three different genera to those in healthy cattle. The moles in the experiment were vaccinated against protein illness to artificially stimulate their immune response. Significant alterations were noted in IgG2, and it was discovered that the distinction between breeds was hindered